2004
DOI: 10.1029/2004gl020892
|View full text |Cite
|
Sign up to set email alerts
|

Are seismic waiting time distributions universal?

Abstract: [1] We show that seismic waiting time distributions in California and Iceland have many features in common as, for example, a power-law decay with exponent a % 1.1 for intermediate and with exponent g % 0.6 for short waiting times. While the transition point between these two regimes scales proportionally with the size of the considered area, the full distribution is not universal and depends in a non-trivial way on the geological area under consideration and its size. This is due to the spatial distribution o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 21 publications
4
82
1
2
Order By: Relevance
“…This defines a correlated behavior for earthquakes separated by short time intervals, while for larger time intervals earthquakes are independent. In later studies the universal behavior in the interevent time distribution has been questioned (Davidsen and Goltz, 2004; The corresponding q-logarithmic distributions ln q (P (> τ )) for the entire dataset (circles) and for M ≥ M c (crosses), exhibiting correlation coefficients ρ = −0.9842 and ρ = −0.9952, respectively. The straight line is the q-exponential distribution.…”
Section: G Michas Et Al: Non-extensivity In Earthquake Sequencesmentioning
confidence: 99%
“…This defines a correlated behavior for earthquakes separated by short time intervals, while for larger time intervals earthquakes are independent. In later studies the universal behavior in the interevent time distribution has been questioned (Davidsen and Goltz, 2004; The corresponding q-logarithmic distributions ln q (P (> τ )) for the entire dataset (circles) and for M ≥ M c (crosses), exhibiting correlation coefficients ρ = −0.9842 and ρ = −0.9952, respectively. The straight line is the q-exponential distribution.…”
Section: G Michas Et Al: Non-extensivity In Earthquake Sequencesmentioning
confidence: 99%
“…Based on studies of all earthquakes in southern California during a prescribed time interval, Bak et al (2002) obtained a universal scaling for the statistical distribution of interoccurrence times. Subsequently, other studies of this type have been carried out (Carbone, et al, 2005;Corral, 2003Corral, , 2004aCorral, , b, 2005aDavidsen and Goltz, 2004;Lindman, et al, 2005;Livina, et al, 2005a, b). Shcherbakov et al (2005) showed that this observed behavior for aftershocks can be explained by a non-homogeneous Poisson process.…”
Section: Introductionmentioning
confidence: 98%
“…The parameter d is thus an important one in statements concerning the universality of the left/right tails in the waiting time distribution (see Davidsen and Goltz, 2004;Corral, 2003).…”
Section: Scaling Of T(l×l): An Empirical Approachmentioning
confidence: 99%
“…When (17) has a power-law singularity at zero. The exponent of this power asymptotic is not universal (see an opposite opinion in (Davidsen and Goltz, 2004)). The statistical difficulties inherent in the analysis of small/large deviations and the potential dependence of the answer on the order of the limiting processes in t and L constitute the main sources of contradictory assertions as to the tails of the distribution of ) ( p L t .…”
Section: The Distribution Of T(l×l) For Small Valuesmentioning
confidence: 99%